HUBUNGAN PENGETAHUAN LINGKUNGAN DAN MOTIVASI HIDUP SEHAT TERHADAP PERILAKU SISWA DALAM KEBERSIHAN LINGKUNGAN SEKOLAH (Survey di MTS N Plupuh Sragen) - ., Wihaji (Green Earth, 2012)
The objective of the research is to study the empirical relationshipsÂ between knowledge of environment (X1), motivation health of life (X2), with act of cleanship at school area (Y). The research consists of 100 respondents with multistage random sampling.technique. The research concludes that there are positive correlations between : (1) knowledge of environment withÂ act of cleanship at school area , (2) motivation health of life with act of cleanship at school area , (3) There are positive relationships betweenÂ knowledge of environment, motivation health of life with act of cleanship at school area. Based on the hypothesis test, the findings showed that first, concerning of level knowledge about the environment (X1) has a positive relationship with studentsâ behavior in the school environment (Y), with a correlation coefficient (ry1) of 0.470 and the regression equation Y = 0.470 + 0.529 X1 Thus the environmental knowledge Â determines the behavior of students in school hygiene. Second, the motivation to live healthy has a positive relationship with the behavior of students in the school environment (Y), with a correlation coefficient (ry2) = 0.567 and the regression equation Y = 41.961 + 0.501 X2 Thus the motivation to live healthy determine the behavior of students in the school hygiene. Third, the environmental knowledge (X1) and the motivation of healthy life (X2) have a positive relationship with the behavior of students in the school environment (Y), indicated by the correlation coefficient (ry12) = 0.45 and multiple regression Y = 16.90 +0.40 +0.38 X1 X2. Thus the environmental knowledge determines the motivation to live healthy and it has contribution significantly to the behavior of students in the school environment hygiene. It can be concluded that the studentsâ behavior toward the school environment can be created through improving the environmental knowledge and strengthening the motivation to live healthy.Â Key words: motivation, environment, behavior